Why are saving rates of urban households in China rising? - Chamon, Marcos; Prasad, Eswar S., 1965- (IMF working paper, 2008)
Paper examines savings rates in urban China from 1995 to 2005. In this period the average urban household saving rate in China rose by 7 percentage points, to a quarter of disposable income. Saving rates increased across all demographic groups, although the saving rates are highest among the youngest and oldest households. The authors attribute these patterns to the rising private burden of expenditures on housing, education, and health care.